'Understanding' for Russia in Germany: international triangle meets domestic politics. Issue 6 (2nd November 2021) - Wood, Steve
Abstract: 'Understanding' for Vladimir Putin's Russia is present across Germany's political spectrum, in business sectors, and within society/the electorate at large. It was boosted by the outcome of the 2017 election which saw a far right party, the Alternative für Deutschland (AfD), join Die Linke, a far left party, as a 'pro-Russia' force in parliament. Together they obtained 22% of the vote. Voices in centre parties also urge 'dialogue' and conciliation with Russia. Extra-parliamentary advocates are more strident in their support. Germany's vulnerable coalition government is confronted by Russian disinformation exploiting historical memory, discontent with policies, and scepticism towards the US, a situation exacerbated by the Trump administration. This combination of developments generates a multidimensional, underestimated, and partly realised potential for more destabilisation of Western alliances and Eurasian security.